낮은 수소농도에서 합성천연가스 생산을 위한 상업용 촉매의 반응특성; 스팀과 CO₂에 대한 영향 - 강석환(Suk-Hwan Kang); 김진호(Jin-Ho Kim); 김효식(Hyo-Sik Kim); 류재홍(Jae-Hong Ryu); 정기진(Ki-Jin Jeong); 유영돈(Young-Don Yoo); 김광준(Kwang-Jun Kim) (Clean Technology, 20(1), 2014)
본 연구에서는 합성천연가스(synthetic natural gas, SNG)를 생산하기 위한 공정 개발을 위해 H2/CO 비가 낮은 합성가스를 이용하여 스팀과 함께 메탄화 반응을 수행하였다. 본 실험과 같은 조건에서는 수성가스 전환반응과 메탄화 반응이 동시에 일어나며, 스팀양이 적을 경우 촉매의 비활성화가 발생할 수 있다. 때문에, 스팀 양에 대한 반응특성을 수행하였으며, 더불어고농도의 CO2가 함유된 합성가스에 대한 메탄화 반응특성도 함께 고찰하였다. 그 결과, 스팀의 공급으로 인하여 촉매 층내의 온도를 낮출 수 있었으며, 메탄화 반응과 수성가스전환반응이 동시에 일어났음을 확인할 수 있었다. 고농도의 CO2가 함유된 합성가스의 메탄화 반응에서는 조금 낮은 메탄 수율을 보였지만, 장기운전(1,000 h) 결과로부터 본 연구에서 수행한 합성가스의 조건을 SNG 공정에 적용이 가능할 것으로 확인되었다. In this work, we performed the methanation with steam and synthesis gas of a low H2/CO ratio to develop a process forproducing SNG (synthetic natural gas). In this experiment conditions, the water gas shift reaction and the methanation reactiontake place at the same time, and insufficient supply of steam might cause the deactivation of the catalyst. Therefore, the reactioncharacteristics with the amount of steam was performed, and the methanation on syngas containing CO2 of the high concentrationwere studied. As a result, the temperature in the catalyst bed decreased by the supply of steam, and the methanation and the watergas shift reaction occurred at the same time. Although methane yield slightly decreased at the methanation using syngascontaining CO2 of the high concentration, the long-term operation (1,000 h) in the experimental conditions of this study indicatesthat this condition is suitable for the new commercial scale SNG process. KCI Citation Count: 3